Organic phototransistors with bulk heterojunction sensing-channel layers containing soluble difluorinated diketopyrrolopyrrole acceptor. (September 2018) - Lee, Chulyeon; Kim, Joonwoo; Moon, Yejin; Kim, Dohan; Han, Hyemi; Kim, Hwajeong; Kim, Youngkyoo
Abstract: Here we report synthesis of a difluorinated diketopyrrolopyrrole (DPP) derivative, 3, 6-bis(5-(( E )-3, 5-difluorostyryl)thiophen-2-yl)-2, 5-bis(2-ethylhexyl)-2, 5-dihydropyrrolo[3, 4- c ]pyrrole-1, 4-dione (EHD3FV), and its application as a photosensing electron acceptor in the bulk heterojunction (BHJ)-type organic phototransistors (OPTRs). EHD3FV was synthesized via the palladium-catalyzed Suzuki cross-coupling reaction between 3, 6-bis(5-bromothiophen-2-yl)-2, 5-bis(2-ethylhexyl)pyrrolo[3, 4- c ]pyrrole-1, 4(2H, 5H)-dione and trans -2(3, 5-difluorophenyl) vinyl boronic acid pinacol ester. The pristine EHD3FV film showed optical absorption up to >850 nm, while its highest occupied molecular orbital (HOMO) energy reached −5.87 eV. The EHD3FV molecules were mixed with poly(3-hexylthiophene) (P3HT) leading the BHJ (P3HT:EHD3FV) sensing-channel layers for OPTRs. The OPTRs fabricated exhibited noticeable photoresponses upon illumination with different wavelengths of visible light (550 nm and 700 nm). The best responsivity (photoresponse) was achieved at the 8:2 (P3HT:EHD3FV) composition, even though the transistor performances in the dark became lower as the EHD3FV content increased. The present result supports the capability of EHD3FV as a photosensing electron acceptor in the BHJ-type OPTRs. Highlights: New difluorinated diketopyrrolopyrrole dye, EHD3FV, is synthesized via Suzuki cross-coupling reaction. EHD3FV exhibits optical absorption up to >850 nm. EHD3FV acts as an electron acceptor for BHJ-type organic phototransistors (OPTRs). OPTRs with the EHD3FV dye can detect photons at the wavelength of >700 nm. The best responsivity is achieved at the EHD3FV content of 20 wt%.